Organic rubrene/topological insulator Bi2Se3/SiO2 hybrid heterojunction photodetectors for broadband and ultrafast photodetection application. Issue 4 (24th December 2021) - Wali, Sartaj; Yin, Qin; Li, Jiao; Si, Guoxiang; Shafi, Muhammad; Ren, Junfeng; Zhang, Hongbin
Abstract : Novel photodetectors have been developed by using the organic/inorganic hybrid heterostructure of the rubrene/topological insulator Bi2 Se3, which demonstrate superior photodetection performance benefiting from the Dirac surface state at the heterointerface. Abstract : Organic–inorganic heterostructures (OIHs) are an emerging topic that has attracted great research enthusiasm due to their unique features for electronic and optoelectronic applications. Although OIHs constructed with topological insulators and organic small molecule semiconductors may have better device performance, this type of heterostructure has rarely been reported, and more research is required to uncover its internal dynamics. Thereby, OIHs based on organic rubrene and inorganic topological insulator Bi2 Se3, which were prepared by employing simple physical vapor deposition, were investigated for the first time. Experimental results proved that the crystalline rubrene and topological insulator Bi2 Se3 films are promising candidates for fabricating high-performance organic–inorganic heterostructure photodetectors (OIHPDs) accompanied by a broadband photodetection range. The Dirac surface state at the heterojunction interface facilitates the dissociation and transportation of photo-generated carriers. Importantly, the OIHPDs displayed excellent diode characteristics with a current rectifying ratio of 460, a maximum responsivity of 8.85 A W −1, a high detectivity of 3.14 × 10 12 Jones, and an ultrafast response speed with τ rise (2.1 μs) and τ decay (2.9 μs) under near-infrared light illumination of 1064 nm, respectively. Due to these interesting results, the OIHPDs can be used in many detection fields, and suggest a promising opportunity for novel device application in the future.